Mobility in a globalised world 2014. - (:unkn) unknown (My University, 2015)
The term mobility has different meanings in the following science disciplines. In economics, mobility is the ability of an individual or a group to improve their economic status in relation to income and wealth within their lifetime or between generations. In information systems and computer science, mobility is used for the concept of mobile computing, in which a computer is transported by a person during normal use. Logistics creates by the design of logistics networks the infrastructure for the mobility of people and goods. Electric mobility is one of today s solutions from engineering perspective to reduce the need of energy resources and environmental impact. Moreover, for urban planning, mobility is the crunch question about how to optimise the different needs for mobility and how to link different transportation systems. In this publication the authors collected the ideas of practitioners, researchers, and government officials regarding the different modes of mobility in a globalised world, focusing on both domestic and international issues.
Keywords: Verkehr; Verkehrstechnologie; Mobilität; Autoverkehr; Verkehrsinfrastruktur; Beschaffung; Logistik; Globalisierung; Nachhaltige Mobilität; Distribution